Cultural Diplomacy in Global Governance: Reimagining Indonesia’s Soft Power Through Nahdlatul Ulama’s Islam Nusantara Paradigm - Muttaqin, Fakih Fadilah; Munandar , Aris; Susanti, Endang; Gutierrez, Yamil Hassan Rozo; Riaz, Farman (JURNAL INDO-ISLAMIKA, 2025)
This study analyzes Nahdlatul Ulama (NU)’s deployment of Islam Nusantara as cultural soft power to counter global Islamophobia. Through case studies of NU’s diaspora networks (PCINU) in Japan and Australia—using interviews, discourse analysis, and policy documents—the research reveals cultural diplomacy strategies: haul (commemorative rituals), shalawatan (devotional chants), interfaith education, and cross-cultural dialogues. These promote moderate Islam rooted in local traditions, contrasting state-centric models (e.g., Saudi Arabia, Iran). Challenges include intra-Muslim fragmentation and Salafi-Wahhabi-driven digital radicalization, yet NU fosters global perceptions of Islam as adaptive and peaceful. The study urges integrating NU’s grassroots efforts into Indonesia’s foreign policy while enhancing multilingual digital counter-radicalization outreach. Theoretically, it redefines soft power by shifting discourse to position civil society as diplomatic agents, demonstrating how religious-cultural movements reshape transnational narratives of Islamic moderation. NU’s model elevates Indonesia’s global image as an inclusive Islamic hub, though sustained impact requires institutional collaboration, resource mobilization, and strategic communication.